2010
DOI: 10.1021/mp9002255
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive Polymeric siRNA Carriers Sensitize Multidrug Resistant Ovarian Cancer Cells to Doxorubicin via Knockdown of Polo-like Kinase 1

Abstract: Small interfering RNA (siRNA)-based therapies have great potential for the treatment of debilitating diseases such as cancer, but an effective delivery strategy for siRNA is elusive. Here, pH-responsive complexes were developed for the delivery of siRNA in order to sensitize drug-resistant ovarian cancer cells (NCI/ADR-RES) to doxorubicin. The electrostatic complexes consisted of a cationic micelle used as a nucleating core, siRNA, and a pH-responsive endosomolytic polymer. Cationic micelles were formed from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 76 publications
2
70
0
Order By: Relevance
“…In addition to the pathways in cancer and pathways related to specified cancers (such as prostate and colorectal cancer), 4 pathways including ErbB signaling, focal adhesion, apoptosis and p53 signaling were enriched, suggesting that HNF1B may contribute to drug resistance in ovarian cancer via those pathways. ErbB signaling (91), focal adhesion (92,93), apoptosis (94,95) and p53 signaling (96,97) have been reported to associate with drug resistance in ovarian cancer. For example, miR-21 regulates drug resistance via apoptosis and cellular survival pathways (94), and loss of DOK2 induces carboplatin resistance in ovarian cancer via suppression of apoptosis (98).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the pathways in cancer and pathways related to specified cancers (such as prostate and colorectal cancer), 4 pathways including ErbB signaling, focal adhesion, apoptosis and p53 signaling were enriched, suggesting that HNF1B may contribute to drug resistance in ovarian cancer via those pathways. ErbB signaling (91), focal adhesion (92,93), apoptosis (94,95) and p53 signaling (96,97) have been reported to associate with drug resistance in ovarian cancer. For example, miR-21 regulates drug resistance via apoptosis and cellular survival pathways (94), and loss of DOK2 induces carboplatin resistance in ovarian cancer via suppression of apoptosis (98).…”
Section: Discussionmentioning
confidence: 99%
“…This is mainly due to poor endosomal escape (pH 5-6.5), and subsequent degradation of the nucleic acid cargo in the late lysosomes (pH ~4.5) by a variety of degradative enzymes (Dominska and Dykxhoorn 2010). It has been recently reported that fusogenic/synthetic peptides and pH-sensitive moieties can be attached to various polymers to assist endosomal escape ( [Meyer et al, 2009], [Hatakeyama et al, 2009], [Carmona et al, 2009] and [Benoit et al, 2010]). These compounds are normally pHtriggered amphiphiles that undergo a surface change in the acidic environment, leading to the release of nanoparticles into the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that ATM and p53 coordinately regulated FoxM1 to modulate responses and resistance to epirubicin in breast cancer [19]. It has been shown that PLK1 plays a role in DNA damage recognition with homologous recombination repair and has been involved in multidrug resistance [44][45][46]. Based on the interaction between FoxM1 and its downstream genes, FoxM1 could be used as a therapeutic target to overcome acquired resistance to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%